Nursery Rhymes (Kuala Lumpur Kohwai & Young, 2009)
This delightful series of books creates a fun learning experience using bright and lively illustrations and photographs that will stimulate young mind. The variety of topics helps children to build the foundation for vocabulary development and early literacy skills. Teachers/Parents can encourage active learning through naming and spotting familiar objects, associating with the words, reading, and the talking about the pictures. It also a useful series for widening the children knowledge
A SUPER SERIES TO DEVELOPING EARLY LITERACY SKILLS
Rhymes & Songs
1 2 14
Keywords: English poetry